Brillouin light scattering spectroscopy of phonons, magnons, and magnetoelastic waves - Nygren, Katherine Elise, author; Buchanan, Kristen S., advisor; Field, Stuart, committee member; Brewer, Samuel, committee member; Shores, Matthew, committee member (Colorado State University. Libraries, 2022)
This thesis discusses three projects that involve the propagation of waves through the utilization of an optical measurement technique known as Brillouin light scattering (BLS) spectroscopy. BLS spectroscopy measurements were completed using a six pass tandem Fabry-Pérot interferometer to detect light that has inelastically scattered from vibrational, spin, or magnetoelastic waves in a sample. This measurement method is noncontact, so wires do not need to be connected to the sample, nondamaging (unless the laser power is too high, and only for sensitive samples), and can detect nonlinear signals. The first project uses an antenna called an interdigital transducer to produce a surface acoustic wave. This wave travels across a piezoelectric substrate and couples to a spin wave in a nickel film. The coupled wave known as a magnetoelastic wave is then studied using BLS as a function of the external applied magnetic field. These results are used to help us understand how the magnetic resonance contributes to the coupled wave. Further BLS measurements as a function of distance across the nickel film are used to calculate a decay length of the magnetoelastic wave two orders of magnitude larger than the decay length for a pure spin wave in nickel. Second, we explore a device using a thin film of an organic ferrimagnet called vanadium tetracyanoethylene (VTCNE) that is magnetic at room temperature and has low damping, which rivals damping in high quality YIG films commonly used in microwave applications. Because VTCNE is oxygen sensitive it is encapsulated between two pieces of glass using an epoxy. The encapsulation does not change the damping, however due to magnetostriction, the strain of the epoxy may change the magnetic properties of the film. To understand how the epoxy strain can effect this device and others with similar encapsulation, we study thermal phonons in the encapsulation materials using Brillouin light scattering. The thermal phonon measurements along with phonon simulations allow us to calculate both the wave speeds and the elastic properties of the materials. These calculated properties can then be used to model future VTCNE devices. The final major project uses BLS spectroscopy to study spin waves in a Y-shaped structure of an iron nickel alloy. Using an in-plane externally applied magnetic field and an antenna across the top of the Y, we excite magnons in each arm of the Y, which then propagate into the base of the Y. BLS measurements are taken in each arm and the base of the Y, as a function of the driving frequency, and a 2D spatial map of the spin waves in the Y-structure was obtained to gain additional information on the modes that propagate past the junction of the Y. The BLS data in conjunction with simulations, demonstrate an indirect way to efficiently excite Damon-Eshbach spin waves as well as convert low wavevector spin waves in the arms of the Y into higher wavevector spin waves as they propagate into the base of the Y. The wavevector conversion and more efficient method of generating Damon-Eshbach spin waves are tools that can be exploited in magnonic device designs. Three additional spin wave projects are also discussed briefly. The projects include a yttrium iron garnet (YIG) confined structure, a VO2 film with a metal-insulator-transition near room temperature, and a heavy metal-ferrimagnet-heavy metal sample that should have a strong interfacial Dzyaloshinskii-Moriya interaction.
Keywords: Brillouin light scattering; magnons; BLS; phonons; magnetoelastic waves